KEPEMIMPINAN DALAM PERNIKAHAN ADAT JAWA DI DESA KARANG GADING: ANALISIS NILAI DAN SIMBOLISME - Hasni Periadi Hasibuan; Selvia Selvia (STKIP Pesisir Selatan, 2025)
Objective: This study discusses the leadership values ​​embodied in Javanese traditional weddings in Karang Gading Village, Labuhan Deli District, Deli Serdang Regency. This research method uses descriptive qualitative with triangulation. Based on the results of interviews with local traditional leaders, it was found that the procession and symbols in Javanese traditional weddings not only have religious and social meanings, but also represent the values ​​of public, organizational, and operational leadership. In the context of public leadership, this tradition teaches moral responsibility, justice, and compassion as the basis for social harmony. Organizational leadership values ​​are reflected through symbols such as the twin mayang, umbrella, and keris which depict cooperation, protection, and decisiveness in decision-making. Meanwhile, operational leadership values ​​are evident in the procession stages such as siraman, midodareni, and sungkeman which contain messages about discipline, respect, and ethical actions. Thus, Javanese traditional weddings in Karang Gading Village not only function as a cultural heritage, but also as a source of leadership learning relevant to modern social life.